Enhanced Heat Transfer of 1-Octadecanol Phase-Change Materials Using Carbon Nanotubes - Xiuli Wang; Qingmeng Wang; Xiaomin Cheng; Yi Yang; Xiaolan Chen; Qianju Cheng (Molecules)
Solid–liquid phase-change materials (PCMs) have attracted considerable attention in heat energy storage due to their appropriate phase-transition temperatures and high thermal storage density. The primary issues that need to be addressed in the wide application of traditional PCMs are easy leakage during solid–liquid phase transitions, low thermal conductivity, and poor energy conversion function. The heat transfer properties of PCMs can be improved by compounding with carbon materials. Carbon nanotubes (CNTs) are widely used in PCMs for heat storage because of their high thermal conductivity, strong electrical conductivity, and high chemical stability. This study investigates the thermal properties of 1-octadecanol (OD) modified with different diameters and amounts of CNTs using the melt blending method and the ultrasonic dispersion method. The aim is to enhance thermal conductivity while minimizing latent heat loss. The physical phase, microstructure, phase-change temperature, phase-transition enthalpy, thermal stability, and thermal conductivity of the OD/CNTs CPCMs were systematically studied using XRD, FTIR, SEM, DSC, and Hot Disk. Moreover, the heat charging and releasing performance of the OD/CNTs CPCMs was investigated through heat charging and releasing experiments, and the relationship among the composition–structure–performance of the CPCMs was established.